Analizando la innovación comercial en las empresas peruanas de manufactura de menor intensidad tecnológica - Del Carpio Gallegos, Javier Fernando (2020)
Non-technological innovation, including organizational and marketing innovation, has attracted substantial interest from researchers. The present study focuses on how external sources of knowledge relate to product, organizational, and marketing innovation, as well as analyzing how product and organizational innovation mediate the relationship between external sources of knowledge and marketing innovation. Current studies on marketing innovation do not present its real impact and importance for manufacturing companies. Using data from 557 Peruvian manufacturing companies that possess lower technological intensity, a model of partial structural equations was applied. The results show that external sources of market knowledge are related to product and organizational innovation. Managers should promote product innovations that favor the development of marketing innovations in the company.